Psychometric Properties Based on Analysis of the Factor Structure of the Generative Altruism Scale Among University Students - Fayek Riyad Al. Serhane (Zanco Journal of Human Sciences, 2025)
The current research aims to identify the psychometric properties and factor structure of the generative altruism scale among university students. The researchers adopted the generative altruism scale from the study (Bussing et al., 2013) and adapted it in an Iraqi cultural context different from the original cultural context of the scale. For this purpose, the researchers translated it using a back-translation method. Then he prepared his instructions and presented it to a group of arbitrators. The researchers adopted the descriptive approach to the research procedures, and a sample was selected according to the Thomson equation, amounting to (378) male and female students from the University of Babylon for the academic year (2023/2024), distributed in a random manner with a proportional distribution using the Cochrane equation, and he The researchers used confirmatory factor analysis, extracting the values of the conformity indicators for the measurement tool, and calculating the validity, reliability, and standard error. The researchers reached several results and came up with a set of conclusions, recommendations, and proposals.